Sperm retrieval techniques for assisted reproduction - Sandro C. Esteves; Ricardo Miyaoka; Ashok Agarwal (International Brazilian Journal of Urology, 2011)
Different surgical methods such as PESA, MESA, TESA, TESE and micro-TESE have been developed to retrieve spermatozoa from either the epididymis or the testis according to the type of azoospermia, i.e., obstructive or non-obstructive. Laboratory techniques are used to remove contaminants, cellular debris, and red blood cells following collection of the epididymal fluid or testicular tissue. Surgically-retrieved spermatozoa may be used for intracytoplasmic sperm injection (ICSI) and/or cryopreservation. In this article, we review the surgical procedures for retrieving spermatozoa from both the epididymis and the testicle and provide technical details of the commonly used methods. A critical analysis of the advantages and limitations of the current surgical methods to retrieve sperm from males with obstructive and non-obstructive azoospermia is presented along with an overview of the laboratory techniques routinely used to process surgically-retrieved sperm. Lastly, we summarize the results from the current literature of sperm retrieval, as well as the clinical outcome of ICSI in the clinical scenario of obstructive and non-obstructive azoospermia.